Early and late results of open surgical and endovascular treatment of infrarenal abdominal aortic aneurysms, selected according to surgical risk - Torres Hernández,José A. (2021)
Abstract Background Open surgical repair (OSR) and endovascular aneurysm repair (EVAR) surgery are alternative treatments for infrarenal abdominal aortic aneurysm (IRAAA). Objectives To compare OSR and EVAR for the treatment of IRAAA. Methods 119 patients with IRAAA were electively operated by the same surgeon between January 1, 2006 and December 31, 2015, following selection for OSR or EVAR according to surgical risk. Complications, reinterventions, failures, and early and late mortality were analyzed. Results 63 OSR and 56 EVAR patients were analyzed. They were similar in terms of age (70 years), gender (92% men), and average diameter of IRAAA (6.5 cm), but with different comorbidities, surgical risk, and anatomy. EVAR was better than OSR regarding time in the operating theatre (177.5 vs. 233.3 minutes), need for transfusion (25 vs. 73%), and length of stay in ICU (1.3 vs. 3.3 days) and hospital (8.1 vs. 11.1 days). OSR allowed more associated procedures to be conducted simultaneously (19.0 vs. 1.8%). There were no significant differences between the groups with respect to complications (25.4 vs. 25.1%), reinterventions (3.2 vs. 5.2%), or early mortality (1.6 vs. 0%). During follow-up, OSR was associated with fewer revisions (3.13 vs. 4.21), angio-CTs (0.22 vs. 3.23), complications (6.4 vs. 37.5%), reinterventions (3.2 vs. 23.2%), and failures (1.6 vs. 10.7%), and had better survival (78.2 vs. 63.2%). Conclusions Correct selection of patients achieves excellent results because it avoids OSR in patients at high risk and avoids EVAR in patients with high anatomical complexity, achieving similar results in the perioperative period, but better results for OSR over the course of follow-up.